2023
DOI: 10.1002/jmv.28756
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of Azvudine versus nirmatrelvir–ritonavir in hospitalized patients with COVID‐19: A retrospective cohort study

Abstract: Chinese guidelines prioritize the use of Azvudine and nirmatrelvir-ritonavir in COVID-19 patients. Nevertheless, the real-world effectiveness of Azvudine versus nirmatrelvir-ritonavir is still lacking, despite clinical trials showing their effectiveness compared with matched controls. To compare the effectiveness of Azvudine versus nirmatrelvir-ritonavir treatments in real-world clinical practice, we identified 2118 hospitalized COVID-19 patients, with a follow-up of up to 38 days. After exclusions and propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 15 publications
4
25
4
Order By: Relevance
“…7 As our study mainly included severe COVID-19 patients in China, the limited efficacy of nirmatrelvir-ritonavir is not surprising. 3,8 While Ma et al found a faster time to nucleic acid negative conversion in patients receiving nirmatrelvir-ritonavir compared to those receiving Azvudine, 1 it did not entirely negate our findings that support the better clinical benefit of Azvudine. 3 Evaluating a drug's effectiveness requires clinical data, rather than piecing together several basic articles to make a speculation solely based on its antiviral effect.…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…7 As our study mainly included severe COVID-19 patients in China, the limited efficacy of nirmatrelvir-ritonavir is not surprising. 3,8 While Ma et al found a faster time to nucleic acid negative conversion in patients receiving nirmatrelvir-ritonavir compared to those receiving Azvudine, 1 it did not entirely negate our findings that support the better clinical benefit of Azvudine. 3 Evaluating a drug's effectiveness requires clinical data, rather than piecing together several basic articles to make a speculation solely based on its antiviral effect.…”
contrasting
confidence: 55%
“…3,8 While Ma et al found a faster time to nucleic acid negative conversion in patients receiving nirmatrelvir-ritonavir compared to those receiving Azvudine, 1 it did not entirely negate our findings that support the better clinical benefit of Azvudine. 3 Evaluating a drug's effectiveness requires clinical data, rather than piecing together several basic articles to make a speculation solely based on its antiviral effect. For instance, remdesivir can effectively inhibit COVID-19 infection in vitro but has no significant effect on COVID-19 patients who are already being ventilated.…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…In regions with limited healthcare resources, patients may be unable to access antiviral agents within 5 days of onset and hospitals are admitting more severe patients. In December 2022, only 9.4%–18.2% of patients with COVID‐19 who were admitted to hospitals were accessible antiviral drugs within 5 days after onset in China 16 . It remains unclear whether patients admitted to hospitals after 5‐day onset, who are typically severe cases, still benefit from antiviral agents.…”
Section: Introductionmentioning
confidence: 99%